Aplikasi Sistem Informasi Geografi untuk Kajian Fluktuasi Muka Air Tanah dan Karakteristik Akuifer di Kecamatan Denpasar Selatan Kota Denpasar - KADEK ARI DEWI WAHYUNI; R. SUYARTO; TATI BUDI KUSMIYARTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Application of Geographic Information System for Study of Water Table Fluctuations and Characteristics of Aquifers in the South Denpasar District The water needs of the population in South Denpasar District vary greatly depending on community activities. The population and activities of the community that need clean water continue to increase, on the other hand the PDAM of Denpasar City is only able to meet the clean water needs of the population of 46.06% (PDAM Kota Denpasar, 2017). People who have not yet connected PDAM services use ground water as an alternative to making dug wells or bore wells. Excessive use of ground water and exceeding safe discharge will affect groundwater degradation. The purpose of this study was to determine groundwater fluctuations and aquifer characteristics.The method used is a field survey method and quantitative descriptive using ArcGIS 10.4 software. The results showed that the dry season water table depth ranged from 0,8 to 5 m and the rainy season ranged from 0,5 to 3,9 m with groundwater fluctuations ranging from 0.04 to 1,3 m. The direction of groundwater flow from the north to the south with degree N 183o E. A good aquifer is composed of medium-sized sand material, and medium sized brown sand material. Limited aquifers are composed of weathered meosen limestone and sea coral with a discharge of 5-10 liters/second.